Blockchain in Finance - Matthew N. O. Sadiku; Uwakwe C. Chukwu; Janet O. Sadiku (Research Parks Publishers, 2023)
Blockchain is basically a ledger of recorded financial transactions. This ledger is distributed, published, and stored in multiple locations. Blockchain is a decentralized record-keeping system that documents all transactions that happened on it. It facilitates safe, easy transactions, and builds trust between trading partners. When trust in the central hubs of finance is being increasingly questioned, decentralized systems like the blockchain that reduce the need for such trust become attractive. Blockchain provides a potentially attractive alternative way to organize modern finance. This paper provides a primer on the use of blockchain technology in finance.